Teachers' Strategies in Developing Students' Character of Independence and Discipline at SD Nurul Islam No. 01 Tawaeli - Muhamad Dzulfaqar J. R; A. Ardiansyah; Sri Dewi Lisnawaty (AT-TA'LIM, 2026)
Abstract: Basic education is the initial stage of character formation which plays an important role in building students' personality and responsibility. The value of independence and discipline are two fundamental aspects that must be developed from an early age so that students are able to manage themselves, time, and responsibilities independently. However, the phenomenon in the field shows that there are still many elementary school students who have not shown an independent and disciplined attitude optimally. This study aims to analyze teachers' strategies in developing students' independence and discipline character and identify obstacles faced in their implementation at SD Nurul Islam No. 01 Tawaeli. This research uses a qualitative approach with a descriptive design. Data is collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing with triangulation techniques to ensure the validity of the data. The results of the study showed that teachers applied several main strategies in character development, namely example, positive habituation, responsibility, and positive reinforcement in the form of praise and appreciation. The obstacles faced include differences in student backgrounds, the influence of the family environment, and the limited time of teachers in intensive character development. This study confirms that consistent and contextual teacher strategies play an important role in shaping students' independent character and discipline in elementary school.